Improving the management of business ecosystems of the border territory (using the example of Russia and China) - F. F. Sharipov; O. A. Timofeev (Путеводитель предпринимателя)
The unique geographical location of our State can be used to develop Russian-Chinese business ecosystem on the border territories. On the basis of the analysis, the authors in their study determine ways to improve the management of the business ecosystems of the border area between Russia and China.